A IMPORTÂNCIA DAS VANTAGENS LOCACIONAIS E DOS SERVIÇOS PRODUTIVOS NAS INDÚSTRIAS AUTOMOTIVAS ASIÁTICAS NO ESTADO DE SÃO PAULO: O CASO DE PIRACICABA, INDAIATUBA E SUMARÉ - Takami, Saulo Teruo [UNESP]; Mendes, Auro Aparecido [UNESP] (Editora da Universidade Federal de Uberlândia - EDUFU, 2022)
The industrial activity, mainly at automotive sector, after the 1970s, started to demand, increasingly, productive services since simple activities, such as: safety, cleanliness, food, for instance, until sophisticated services (marketing, design, computer, among others). This kind of service involves a group of activities that may be intensive in capital, technology and highly skilled labour. The implantation of Hyundai in Piracicaba city, in 2012; Toyota in Indaiatuba city, in 1998 and Honda in Sumaré city, in 1997, reveals the importance of countryside of São Paulo state in attraction of Asian industries. The present paper has the objective to analyse the importance of local advantages and productive services at Asian industries in mentioned cities that represent the spatial area of this research. Besides the introduction and final considerations, this paper will deal the conceptual aspects and the typology of services to industrial activity; the importance of local advantages to Asian automotive industries in São Paulo state and the relevance of productive services and other locational factors to automotive industries researched.

A atividade industrial, especialmente no setor automotivo, a partir da década de 1970, passou a demandar cada vez mais serviços produtivos desde atividades mais simples, tais como: segurança, limpeza, alimentação, por exemplo, até serviços mais sofisticados (marketing, design, informática, dentre outros). Tais serviços envolvem uma gama de atividades que podem ser intensivas em capitais, tecnologias e mão de obra altamente especializada. A implantação da Hyundai em Piracicaba, em 2012; da Toyota em Indaiatuba em 1998 e da Honda em Sumaré em 1997, revela a importância do interior do estado de São Paulo na atração de indústrias asiáticas. O presente artigo tem por objetivo analisar a importância das vantagens locacionais e dos serviços produtivos nas indústrias asiáticas nos municípios mencionados que constituem o recorte espacial dessa investigação científica. Além da introdução e das considerações finais, serão abordados os aspectos conceituais e as tipologias dos serviços para a atividade industrial; a importância das vantagens locacionais para as indústrias automotivas asiáticas no estado de São Paulo e a relevância dos serviços produtivos e de outros fatores locacionais para as indústrias automotivas pesquisadas.
The importance of local advantages and productive services in asian automotive industries in São Paulo state: the case of Piracicaba, Indaiatuba and Sumaré
Keywords: Local Advantages; Productive Services; Asian Automotive Industries; Vantagens Locacionais; Serviços Produtivos; Indústrias Automotivas Asiáticas